Analysis of the Functional Policy Strategy of the Republican Ombudsman: Analisis Strategi Kebijakan Fungsional Ombudsman - Rizky B, Dandi Amar; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
The establishment of the Ombudsman of the Republic of Indonesia aims to help create and develop conducive conditions in carrying out the eradication of maladministration. In the process of providing public services, the supervision of public service problems in East Java by the Indonesian Ombudsman Representative of East Java is still said to be ineffective. The purpose of this study is to identify, describe and analyze the Strategy and Functional Policy of the Ombudsman of the Republic of Indonesia for the Representative of East Java. Qualitative descriptive research method through interviews, observation and documentation. Technical analysis of data using Miles and Hubberman through data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Strategy and Functional Policy also focuses on a strategic step that is very important to do, a problem that is quite severe with the culture of the community carrying out extortion actions that were carried out intentionally with the reason of "pity" and "don't want to be complicated". This was done intentionally.